Developing An Integrated Digital Communication Model For Institutional Image Enhancement In Higher Education - Megasari Noer Fatanti; Zainal Fatah; Shofwa Hilyatul Auliya (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Digital transformation compels higher education institutions to adapt communication strategies to fortify their institutional image, a strategic asset significantly shaped by the quality of digital interactions. This study analyzes the digital communication practices within public services at the Faculty of Social Sciences, Universitas Negeri Malang (FIS UM), to formulate an optimization model. Employing a qualitative-descriptive method, data were collected through in-depth interviews with stakeholders, digital observation of official platforms, and document analysis. The findings reveal that current communication is predominantly reactive, fragmented, and strategically misaligned with audience needs. Furthermore, an underdeveloped user interface and experience (UI/UX) on the faculty’s digital platforms fail to project a professional image and hinder user engagement. Concluding that a coherent digital communication strategy is absent, this research proposes an Integrated Service Unit (ULT) as its primary contribution. The model’s novelty lies in its function as a proactive instrument for reputation management, transforming disparate interactions into a cohesive strategy for measurably strengthening the institutional image.